Ethnicity and Voting Patterns in the 2007 and 2012 Gubernatorial Elections in Jakarta - Wahyu Prasetyawan (Journal of Current Southeast Asian Affairs, 2014)
This paper evaluates the dynamics of ethnicity and politics in the 2007 and 2012 gubernatorial elections in Jakarta. Previous research has mostly emphasised the negative impact of ethnicity on politics in the reformasi era, particularly through ethnic polarisation. By closely evaluating the major ethnic groups living in the mega-city, i.e. the Javanese, Betawi and Chinese, the author shows that the relationship between ethnicity and voting patterns is an intricate one that is not static, particularly if one evaluates a commonly overlooked but crucial factor – the time frame. The author argues that ethnicity continues to play a role in elections even though it is less significant than education and flood variables. The relationship between ethnicity and voting patterns is thus very dynamic, being related to the political context at the time of an election. The findings in this paper open up new questions on ethnicity and politics in a plural society like Indonesia.